Intracardiac conduction defects in dystrophia myotonica. Electrophysiological study of 12 cases. Issue 3 (March 1980) - Komajda, M; Frank, R; Vedel, J; Fontaine, G; Petitot, J C; Grosgogeat, Y
Abstract : Twelve patients with dystrophia myotonica had cardiac electrphysiological study for conduction disturbances (five cases) or for syncope (seven cases). Conduction disturbances were found in each case, being intranodal in two cases, intra-Hisian in three cases, or diffuse in seven cases. These findings are in agreement with those previously reported, and may be related to the high incidence of sudden death in these patients. Pacemakers are advocated in symptomatic patients, and in some asymptomatic patients with severe and diffuse lesions.